Harnessing Lithium‐Mediated Green Ammonia Synthesis with Water Electrolysis Boosted by Membrane Electrolyzer with Polyoxometalate Proton Shuttles - Miao, Jun; Chen, Cailing; Cao, Li; Al Nuaimi, Reham; Li, Zhen; Huang, Kuo‐Wei; Lai, Zhiping (Angewandte Chemie International Edition, 2025)
Integrating water electrolysis (WE) with lithium‐mediated nitrogen reduction (Li‐NRR) offers a sustainable route for green ammonia production by directly utilizing protons from water oxidation, eliminating reliance on grey or blue hydrogen. Here, polyoxometalates (POMs) function as electron‐coupled proton buffers (ECPBs) to seamlessly link WE with Li‐NRR in a three‐compartment flow reactor comprising an aqueous anode, an organic cathode, and a gas feed chamber. POMs serve as proton shuttles while suppressing the competing hydrogen evolution reaction (HER), facilitating efficient ammonia synthesis. The addition of polymethyl methacrylate (PMMA) enhances catholyte hydrophobicity, mitigating water contamination. By optimizing ECPB concentration, a dynamic balance is achieved between lithium nitride intermediates (LiNxHy) formation and consumption, yielding ammonia at 573.7 ± 5.2 µg h⁻¹ cm⁻2 with a Faradaic efficiency of 54.2%. This design advances flow reactor technology by uniquely utilizing water oxidation as a direct proton source, bypassing conventional hydrogen oxidation methods. The use of POMs as proton shuttles establishes a new benchmark for green ammonia production, reinforcing its potential in sustainable chemistry. This study pioneers a sustainable approach to ammonia synthesis by integrating lithium‐mediated nitrogen reduction (Li‐NRR) with water electrolysis (WE). Polyoxometalates (POMs) serve as electron‐coupled proton buffers (ECPBs), enhancing proton transfer while suppressing hydrogen evolution. A three‐compartment flow reactor achieves continuous ammonia production, setting a benchmark for eco‐friendly nitrogen fixation.